BOUNDEDNESS OF COMMUTATORS OF FRACTIONAL INTEGRAL OPERATORS ON GENERALIZED MORREY SPACES - Oktarini, Silvia
In this thesis, we will discuss about boundedness of commutators of fractional integral operators [b, I?] on generalized Morrey spaces Lp,?(Rn) where b is a bounded mean oscillation or BMO function with several assumptions that must be satisfied. However, we will first discuss the boundedness of the commutator operator [b, I?] on the Lebesgue space contained in the Chanillo result [1]. In [1], there is restriction of ? conditions must be satisfied, but based on the result of Shirai [14] showed that the restriction can be removed. After that, we can prove that the commutator operator [b, I?] is also bounded on generalized Morrey spaces